Evaluation of biorational insecticides to control of whitefly (Bemisia spp.) in tomato cultivation (Journal on studies and research of academic knowledge, 2021)
The tomato is the most consumed vegetable, in terms of volume, by the Paraguayan population and the whitefly is one of the main pests of its cultivation. For the control of this insect, which causes direct and indirect effects on the crop, chemical formulations are used mainly in Paraguay and there is little or no application of alternative (biorational) products due to the lack of a formulated product or lack of knowledge of its efficacy. The experimental design was randomized complete blocks, with ten treatments and two repetitions. The treatments were 5 biorational insecticides and 5 chemical insecticides: Melia azedarach L. leaf extract, Azadirachta indica A. leaf extract, Allium sativum L. plus Capsicum frutescens L. in commercial presentation, liquid soap, detergent plus edible oil, acetamiprid plus pyriproxyfen, lamdacialothrin, imidacloprid, thiamethoxam, and acefate. The variable measured was the number of live nymphs. The nymphs count is performed at 3, 7 and 14 days after the application; resulting that at 7 days the T6 (Acetamiprid + Piriproxifen) presented the least infestation meeting 71.58 live nymphs and, at 14 days, the treatments with the least number of nymphs were T9 (Tiametoxam), T6 (Acetamiprid + Piriproxifen) and T5 (detergent + oil edible) with 44,33, 52,42 and 53 live nymphs respectively. The level of control of Bemisia spp. obtained by this biorational positions it as an option in the integrated management of the insect.
Keywords: Whitefly; Tomato; Biorational insecticides